Element Synthesis of the Educational Management to Digital Mass Communication Graduates Development - ปาปัดถา ฉันทนา (RMUTP Research Journal Humanities and Social Sciences, 2019)
The purpose of the study was to synthesize the element of educational management to develop graduates of mass communication officer in digital age according to the views of experts. The data were collected by an in-depth interview and a content synthesis from 16 experts who were administrators of the university and organization of mass communication. It was found that: There were three main elements and 28 minor ones of educational management forms as follows: (1) Curriculum: knowledge of mass communication, perception of media contexts, interdisciplinary knowledge, writing and communication skill, and the integration of contents. (2) Learning management: analysis thinking development, critical thinking development, creative thinking development, communication skill, flexible learning, cooperative learning, action learning, experiential learning to build new paradigm, development of morals and work ethics, professional skills, integration and content management, media convergence and cross-platform media, nurturing of volunteering spirit and social responsibility, technology literacy skills, technical visits to mass communication organization. (3) Learning environment: sufficient equipment, updated technology, work space, sightseeing, activity corner, covered network and accessibility, news and information corner, and student work exhibition corner.